Avaliação institucional do Instituto Federal da Paraíba: um diagnóstico a partir das avaliações externas - Nascimento, Dhieggo Glaucio Evaristo Gomes (2020)
The Federal Institute of Education, Science and Technology of Paraiba (IFPB), which integrates the Federal Network of Professional, Scientific and Technological Education, is as a Higher Education Institution (HEI) that offers face-to-face classes and distance learning as well. The objective of this research was the elaboration of an IFPB diagnosis, based on a SWOT analysis of the external, on-site and distance learning institutional evaluation reports, therefore, elaborate an examination/evaluation of the current IFPB scenario and proposing suggestions and procedures in favour of the institution, actions that should be responsibility of the Evaluation Committees. The methodology which was used in this study was qualitative based, as well as the use of a theoretical and methodological assumptions of exploratory, bibliographic and documentary research. It was carried out a thorough analysis of the external, on-site (2018) and distance learning (2019) institutional evaluation reports, published on the IFPB website by the Evaluation Committees, through the SWOT administration tool, indicating strengths, weaknesses in the internal environment, as well as opportunities and threats in the external environment, producing an institutional diagnosis, listing the definition of priorities for improving the quality of the HEI. The decision of this methodology was due to the understanding that it allows us to observe the performance of the HEI in Institutional Assessments, as well as identifying how it is working in relation to the instruments, the improvement of institutional quality, in relation to what the current legislation advocates. In the results, it is possible to identify in the SWOT matrix the indicators, which were considered institutional strengths, weaknesses present in some indicator that can be developed, elaborating indicators that we have categorized as threats and opportunities in the external environment in this matrix. Regarding the threats which were identified, it is possible to highlight the budget reduction of the HEI, due to the budgetary instability of the State, besides the fact that the IFPB graduate programs have a concept of level 3, regarding the Coordination for the Improvement of Higher Education Personnel (CAPES), the same score attributed to indicator 3.3 of axis 3 (Distance Learning). Despite these mentioned facts, the institution is a well evaluated HEI, obtaining a score of level 4 in the institutional assessment and a final score of level 5 in the distance education assessment.